A Longitudinal Examination of Social Participation, Loneliness, and Use of Physician and Hospital Services. (April 2015) - Newall, Nancy; McArthur, Jennifer; Menec, Verena H.
Objective: This study examined whether social participation and loneliness predicted health care service use (physician visits, hospitalizations, length of stay in hospital).Method: Participants' ( N = 954; 54% female; aged 45+ years) health data were tracked over 2.5 years following in-person interviews.Results: Being lonely was associated with greater number of physician visits, though this relationship was mediated by health. Neither loneliness nor social participation was associated with admission to hospital. However, for those who were hospitalized at least once over 2.5 years, being lonely was associated with a higher odds of being re-hospitalized; furthermore, greater social participation was associated with a lower odds of being in the hospital for an extended duration. These relationships held even when controlling for initial health.Discussion: Results provide evidence, using objective health care data, of the potential importance of social factors in predicting adults' physician visits, re-hospitalization, and length of stay in hospital.